Association between circadian rhythm and sleep quality among nursing interns: A latent profile and moderation analysis - Wu, Xiaona; Lu, Yingzi; Xie, Xian; Chen, Rongjie; Zhang, Ningning; Zhou, Chen; Ye, Zengjie (Frontiers in Neuroscience, 2022)
Background: Circadian rhythm disturbances are common in night-shift workers resulting in poor sleep quality. The heterogeneity of circadian rhythm and its relationship with sleep quality in nursing interns is less explored. It was designed to identify latent subtypes of circadian rhythm, explore the relationship between circadian rhythm profiles and sleep quality, and evaluate the moderating role of circadian rhythm types between perceived stress and sleep quality in nursing interns. Materials and Methods: 452 nursing interns were recruited from Be Resilient to Nursing Career between October 2020 and January 2021 and administered with 10-item Chinese Perceived Stress Scale, Circadian Type Inventory, and Pittsburgh Sleep Quality Index. Latent profile analysis and moderation analysis were performed. Results: 72.3% of nursing interns reported poor sleep quality. Three latent subtypes of circadian rhythm were identified: Vigorous (40.1%), Inadaptability (18.6%), and Flexibility (41.1%). Female (OR=1.97, 95% Cl 1.01-3.83, P=0.047) with normal Body Mass Index (OR=1.62, 95% CI 0.95-2.76, P=0.078) were prone to Flexibility. Circadian rhythm types significantly moderated the association between perceived stress and sleep quality (P<0.05). Conclusions: There exists heterogeneity of circadian rhythm subtypes in nursing interns and attentions should be paid to those with Inadaptability type.